EFFICACY OF NORGESTOMET REUSED IMPLANTS ON THE ESTROUS CYCLE CONTROL IN DAIRY GOATS - Cruz, Maria Helena Coelho; da Cruz, Jurandir Ferreira; Moura, Luís Cláudio de Oliveira; Neto, Milton Rezende Teixeira; Ferraz, Rita de Cássia Nunes; Silva, Sandra Cristina Becker; Snoeck, Paola Pereira das Neves (Brazilian Journal of Veterinary Medicine, 2010)
ABSTRACT. Cruz M.H.C., Cruz J.F., Moura L.C.O., Teixeira Neto M.R., Ferraz R.C.N., Becker-Silva S.C. & Snoeck P.P.N. [Efficacy of Norgestomet reused implants on the estrous cycle control in dairy goats]. Eficácia de implantes de Norgestomet reutilizados no controle do ciclo estral de cabras leiteiras. Revista Brasileira de Medicina Veterinária, 32(4):219-224, 2010. Curso de Medicina Veterinária, Departamento de Ciências Agrárias e Ambientais, Universidade Estadual de Santa Cruz, Rodovia IlhéusItabuna, km 16, Salobrinho, Ilhéus, BA 45662-000, Brasil. E-mail: paolasnoeck@uesc.br The aim of this study was to evaluate the efficacy of short-term hormonal treatments using Norgestomet reused implants on the estrous cycle control in dairy goats. Thirty five goats were divided in five homogeneous groups of seven animals each one. All female from the groups T1, T2 and T3 received 1/3 of Norgestomet implant of 1st, 2nd and 3rd use, respectively, + eCG (260 IU) + cloprostenol (75 μg); in the T4 group, ½ Norgetomet implant of 2nd use + eCG (260 IU) + cloprostenol (75 μg) and the T5 group, sponge impregnated with MAP + eCG (260 IU) + cloprostenol (75 μg). The AI was developed 45±1 hours after finishing hormonal treatment. In data analysis the Qui-square test was used to compare hot female number and pregnant rate while the characteristics: the final interval of the treatmentonset estrus (FT-OE), and estrus length (EL), were compared by Duncan tests using the statistic software (SAEG, 2000). The estrus behavior was observed in 100.0%, 85.7%, 85.7%, 100.0% and 100.0% of goats from T1 to T5 groups, respectively. The FT-OE intervals in the T3 and T4 (17.0±5.9 h and 15.4±9.1 hours) were smaller (P<0.05) than T1, T2 and T5 groups (29.1±15.3; 23.0±7.0 and 30.0±6.9 hours; in the same order), which did not differ from each other. The T1 and T3 groups, showed a bigger and a smaller variation on the FTOE interval, respectively (48 and 12 hours). The estrus length was similar in all groups (24.9±9.4; 28.0±9.8; 27.0±6.3; 22.3±5.7 and 24.0±6.9 hours; from T1 to T5). The pregnant rate of the T3 group (14.3%) was smaller (P<0.05) than other groups T1, T2 and T5 that did not differ from each other (71.4%; 71.4%; 85.7% and 71.4%, to T1, T2, T4 and T5, respectively). In conclusion, the use of 1/3 of 3rd use implant, although being effective for estrus induction, it doesn’t provide a satisfactory pregnant rate. On the other hand, the fractions of 1/3 of 1st and 2nd use implant of Norgestomet are efficient for estrus and ovulation synchronization, making possible to achieve satisfactory pregnant rate and recommend its use in fixed-time artificial insemination programs in dairy goats.